Zeolites and ordered mesoporous materials : progress and prospects : the 1st FEZA School on Zeolites, Prague, Czech Republic, August 20-21, 2005 /: progress and prospects : the 1st FEZA School on Zeolites, Prague, Czech Republic, August 20-21, 2005. (2005) - Unknown
No abstract available